Centrum handlowe jako czynnik ruchotwórczy w transporcie samochodowym – przykład Portu Łódź = A shopping centre as a traffic-generating factor In car transport as exemplified by Port Łódź, Poland - Kowalski, Michał; Wiśniewski, Szymon (IGiPZ PAN, 2017)
The article presents results of research devoted to the role of the shopping centre as a traffic-generating factor in individual-car transport. The research procedure was conducted in relation to Port Łódź, one of thirteen shopping centres within the boundaries of the Polish city of Łódź. The main aim has been to determine the share of car traffic generated by Port Łódź in the totality of traffic flows in the network of roads leading to the shopping centre. The analysis was based on data from the urban traffic control system or, to be precise, one of its subsystems which has access to information on spatial and time accessibility of the number of vehicles, transmitted from induction loops situated in the network of urban crossroads. The research focuses on defining potential and real traffic generation for weekdays and weekends, as well as during public holidays and festival days. The research allowed for verification of one of the model approaches to the correlation between selected characteristics of shopping centres and the volume of traffic they generate. Results show that shopping centres located along exit roads on the city outskirts affect the road transport system, particularly by exciting car traffic (also during rush hours), retaining it during afternoon rush hours (thus contributing to an alleviation and extension in time) and, to a lesser extent, serving as an informal element of the Park&Ride system (in the case of centres characterised by good accessibility to public transport and a free car park).
24 cm
Keywords: transport geography; traffic-generating; car transport; shopping centre; Łódź